A Framework for Exercising Voting Rights from Anywhere Using ICT Infrastructure: A Cross Sectional Study - Shalabh Agarwal; Asoke Nath; Dipayan Chowdhury (Recent Advances in Mathematical Research and Computer Science Vol. 8, 2022)
In the past days the voting methods was manual system and it was very much booth dependent. There was a geographical barrier. The voter can cast his/her vote only from a particular booth. Since the voting process was through ballot paper and hence after the entire voting process all ballot papers to be checked manually before counting. The idea of this framework is to free an electorate from the binding of voting in an assigned polling centre and enable the voter to exercise his/her voting right from any one of the polling centres spread across a state or a country. This method was reliable but unscientific. So slowly this method of voting is been changed. Now in most of the developing countries, the process of political election for a democratic government is mainly confined to collecting the votes in the particular constituency of a voter. This means that the electorate can cast his/her voting rights only in a particular polling centre assigned to the voter. In this paper the authors have tried to explore the difficulties of voting confined to a polling centre and suggest a framework for the use of ICT infrastructure to get rid of these difficulties.